Studies in rabbinic Judaism and early Christianity : text and context - Jaffé, Dan, 1970- (Ancient Judaism and Early Christianity, 2010)
The question of the origins of Christianity is a theme still discussed in historical research. This book investigates the relations between the Rabbinic Judaism and the Primitive Christianity. It studies the factors of influences, the polemics in the texts and factors of mutual conceptions between two new movements: Rabbinical Judaism and Primitive Christianity. Finally it offers an analysis of the perception of Christianity in the corpus of talmudic literature. La question des origines du christianisme est un thème encore débattu par la recherche historique. Cet ouvrage choisi d'explorer les relations entre le judaïsme rabbinique et le christianisme primitif. Il étudie les facteurs d'influences, les polémiques dont témoignent les textes et les emprunts réciproques entre les deux mouvements naissant : le judaïsme rabbinique et le christiansime primitif. Il propose également une analyse sur la perception du christianisme à l'oeuvre dans la littérature talmudique.